Clinical, dermoscopic and histopathologic findings of retiform hemangioendothelioma - Amanda Mota; Giuseppe Argenziano; Iris Zalaudek; Simonetta Piana; Caterina Longo; Elvira Moscarella; Aimilios Lallas (Mattioli1885, 2013)
Retiform hemangioendothelioma (RH) is an uncommon vascular neoplasm of borderline malignancy that clinically develops as a solitary, gradually enlarging exophytic mass, nodule or plaque, most often on the lower limbs, upper limbs and trunk. Clinical recognition of RH is troublesome because of its non-specific appearance, with differential diagnosis comprising a variety of benign and malignant tumors clinically presenting as reddish nodules. In this article we describe the clinical, dermoscopic and histopathologic findings in a case of RH developing on the flank of a 26-year-old woman, and discuss the possible role of dermoscopy in facilitating the clinical recognition of this rare tumor.